2019
DOI: 10.1097/hcr.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Utilization During an Acute Cardiac Hospitalization

Abstract: Background: Inpatient cardiac rehabilitation (ICR) programs provide important services to hospitalized patients by delivering risk factor education, daily ambulation, and facilitation of referral to outpatient cardiac rehabilitation. However, little is known about ICR utilization or practice patterns. Methods: We examined the use of ICR, between January 2007 and June 2011, in a geographically and structurally diverse sample of US hospitals (Premier, Inc.). Results: Among 458 hospitals, there were 1 343 537… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Similar results have been reported in other studies: participation rates were higher in patients who had undergone cardiac surgery or had AMI and were lower in patients with medically managed HF or stable AP. 11,22 Furthermore, the present study showed that the annual increases in the ICR participation rates were significantly lower in patients with AP and PAD than in patients with AMI, PCS, and HF. Rehabilitation for postoperative patients is likely to be included as part of the postoperative care, which aims for functional recovery and the prevention of complications.…”
Section: Progress Of Icr and Ocr Implementation And Participationsupporting
confidence: 49%
“…Similar results have been reported in other studies: participation rates were higher in patients who had undergone cardiac surgery or had AMI and were lower in patients with medically managed HF or stable AP. 11,22 Furthermore, the present study showed that the annual increases in the ICR participation rates were significantly lower in patients with AP and PAD than in patients with AMI, PCS, and HF. Rehabilitation for postoperative patients is likely to be included as part of the postoperative care, which aims for functional recovery and the prevention of complications.…”
Section: Progress Of Icr and Ocr Implementation And Participationsupporting
confidence: 49%
“…Moreover, the adherence of CR in this study needs to be improved. Less than 40% of patients completed CR, however, the completion of CR is a critical element to ensure the benefit of CR [38]. Most patients gave up the rehabilitation procedure because the benefits of CR did not seem obvious in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital exercises include breathing techniques, transfer between bed and chair, and walking along the ward. In the U.S.A., almost 20% of patients after cardiac surgery received no physical therapy or inpatient cardiac rehabilitation, and when this is utilized, often less than 30% of the hospital days are covered [ 8 ], without weekend day services [ 9 ]. Although interventions are hard to compare, the early mobilization of patients might improve physiological functional capacity, might accelerate recovery, and might reduce hospital length of stay [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%